Flame retardant nonwoven fabric and preparation process
By using metal hydroxide, polyvinyl alcohol, and cyclic paste, the flame retardant non -woven fabrics are used to solve the problem of decreased flame retardant performance and environmental impact in existing technologies, and achieve efficient and persistent flame retardant performance.
Patent Information
- Application Number
- CN202310448940.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-04-24
AI Technical Summary
The flame retardant non-woven fabrics have deteriorated flame retardant properties after friction, and the added flame retardant is harmful to the environment or has poor compatibility.
Materials such as metal hydroxide, polyvinyl alcohol, and cyclic paste are used to prepare flame retardant non -woven fabrics through steps such as soaking, spraying and curing. Improve flame retardant performance.
The prepared flame retardant non -woven fabric has good flame retardant performance. It can still maintain high flame retardant performance after multiple frictions. The limit oxygen index reaches more than 40 %, the damage length is less than 50mm, and the performance changes after 2000 frictions after friction The rate is below 2 %.
Smart Images

Figure BDA0004196821230000041 
Figure BDA0004196821230000061 
Figure BDA0004196821230000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of non-woven fabrics, and in particular to a flame-retardant non-woven fabric and a preparation process thereof. Background Art
[0002] Non-woven fabrics are made of synthetic fibers such as polypropylene, polyester, nylon, etc., and are finished after being spunlace, needle punching or hot rolling reinforcement. Due to their light weight, softness and breathability, non-woven fabrics are currently widely used in medical and health, clothing, packaging and other fields.
[0003] Most of the raw materials used to make non-woven fabrics are flammable, and when burning, they are accompanied by thick smoke and dripping molten materials, which are very dangerous in fires. With the improvement of people's living standards and the enhancement of safety awareness, the flame retardancy of non-woven fabrics has become more and more the focus of people's attention.
[0004] At present, there are two main methods for preparing flame-retardant non-woven fabrics. One is to achieve the flame-retardant function by adding bromine and antimony compounds to the non-woven fabrics. Bromine and antimony compounds will produce harmful substances during the combustion process, which are easy to affect the environment; the other is to achieve the flame-retardant function by adding halogen-free substances such as hydroxides and phosphorus-containing flame retardants to the non-woven fabrics. Although halogen-free substances have flame-retardant properties, halogen-free flame retardants are not compatible with non-woven fabrics. During the long-term use of non-woven fabrics, the folding and friction of non-woven fabrics can easily lead to the loss of flame retardants, affecting the flame retardant properties of the non-woven fabrics. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present application is to provide a preparation process of a flame retardant non-woven fabric, which is simple and easy to implement.
[0006] The second object of the present application is to provide a flame retardant nonwoven fabric, which has good flame retardant properties and can still maintain good flame retardant properties after multiple frictions.
[0007] To achieve the above first purpose, this application provides the following technical solutions:
[0008] A preparation process of a flame retardant nonwoven fabric comprises the following steps:
[0009] S1. The metal hydroxide, polyvinyl alcohol and water are mixed in a weight ratio of (1-3): (10-20): (70-80) to obtain a flame retardant finishing liquid;
[0010] S2. The nonwoven fabric substrate is immersed in the flame retardant finishing solution, removed and dried;
[0011] S3. spraying a coating liquid onto the dried nonwoven fabric after treatment in step S2, wherein the coating liquid comprises a cyclodextrin solution;
[0012] S4. Soak the non-woven fabric treated in step S3 in a curing agent solution, take it out, wash it, and dry it to obtain the flame-retardant non-woven fabric.
[0013] By adopting the above technical scheme, when the non-woven fabric burns, the metal hydroxide absorbs heat, thereby quickly reducing the temperature of the surface of the non-woven fabric fiber, thereby inhibiting the combustion of the non-woven fabric and playing a flame retardant role; there is a hydrophobic interaction between polyvinyl alcohol and the non-woven fabric fibers, and there is a chelating effect between polyvinyl alcohol and the metal hydroxide, so the addition of polyvinyl alcohol helps to improve the compatibility between the metal hydroxide and the non-woven fabric fibers; cyclodextrin covers the surface of the non-woven fabric fibers, which helps to reduce the loss of metal hydroxide during the use of the non-woven fabric; at high temperature, cyclodextrin is carbonized to form a covering layer on the surface of the non-woven fabric fibers, and the covering layer is heat-insulating, oxygen-isolating, and prevents the escape of combustible gases, further improving the flame retardant properties of the non-woven fabric; the curing agent cross-links the polyvinyl alcohol to form a network structure, and the metal hydroxide particles are dispersed in the network structure, which improves the tightness of the metal hydroxide on the surface of the non-woven fabric. At the same time, the curing agent also cross-links the polyvinyl alcohol and cyclodextrin, which improves the tightness of the cyclodextrin on the surface of the non-woven fabric.
[0014] Furthermore, the metal hydroxide is selected from one or both of magnesium hydroxide and aluminum hydroxide, and the average particle size of the metal hydroxide is 50-500 nm.
[0015] By adopting the above technical scheme, magnesium hydroxide or aluminum hydroxide has a large heat capacity and can quickly absorb heat to reduce the temperature of the non-woven fabric surface, thereby playing an effective flame retardant role; the appropriate particle size helps to improve the compatibility between the metal hydroxide and polyvinyl alcohol, thereby increasing the degree of adhesion of the metal hydroxide to the non-woven fabric surface; if the particle size is too large, the metal hydroxide is not firmly attached to the non-woven fabric surface, and if the particle size is too small, the metal hydroxide is easy to agglomerate, which will also affect its adhesion effect on the non-woven fabric surface.
[0016] Furthermore, the degree of polymerization of the polyvinyl alcohol is 1700-1750, and the degree of alcoholysis is 87%-89%.
[0017] By adopting the above technical solution, appropriate degree of polymerization and degree of alcoholysis are helpful to improve the compatibility between metal hydroxide and polyvinyl alcohol, and between polyvinyl alcohol and non-woven fabric substrate.
[0018] Furthermore, the cyclodextrin solution is a cyclodextrin aqueous solution with a concentration of 1-2%, and the spraying amount of the spraying liquid is 3-5g / m 2 .
[0019] By adopting the above technical solution, appropriate concentration and spraying amount are helpful to improve the adhesion efficiency of cyclodextrin on the surface of non-woven fabric.
[0020] Furthermore, the curing agent solution is obtained by mixing a curing agent and a solvent in a weight ratio of (0.1-0.3):100, the curing agent is selected from one or more of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate, and the solvent is selected from one or two of acetone and ethyl acetate.
[0021] By adopting the above technical scheme, the diisocyanate curing agent cross-links the polyvinyl alcohol to form a network structure, and the metal hydroxide particles are dispersed in the network structure, thereby improving the tightness of the metal hydroxide adhesion to the surface of the non-woven fabric; at the same time, the curing agent also cross-links the polyvinyl alcohol and cyclodextrin, thereby improving the tightness of the cyclodextrin adhesion to the surface of the non-woven fabric.
[0022] Furthermore, the spraying liquid also includes metal oxide, the concentration of the metal oxide in the spraying liquid is 1-3%, the metal oxide is selected from one or more of zinc oxide, aluminum oxide, and magnesium oxide, and the average particle size of the metal oxide is 0.5-200 μm.
[0023] By adopting the above technical scheme, on the one hand, the metal oxide forms a flame retardant barrier on the surface of the non-woven fabric, further improving the flame retardant properties of the non-woven fabric; on the other hand, the metal oxide forms a wear-resistant layer on the surface of the non-woven fabric, further reducing the loss of the metal hydroxide flame retardant in the non-woven fabric substrate during the friction process; controlling the particle size of the metal hydroxide within an appropriate range helps to improve the wear resistance of the non-woven fabric surface. If the particle size is too large, the metal oxide is not firmly attached to the non-woven fabric surface. If the particle size is too small, the metal oxide is not effective in improving the wear resistance of the non-woven fabric.
[0024] Furthermore, the spraying liquid also includes polyamino acid, the concentration of the polyamino acid in the spraying liquid is 2-4%, and the polyamino acid is selected from one or more of polyglutamic acid, polylysine, and polyaspartic acid.
[0025] By adopting the above technical solution, there is a chelating effect between the polyamino acid and the metal oxide, and the cyclodextrin and the polyamino acid synergistically help to improve the compatibility between the metal oxide and the non-woven fabric.
[0026] To achieve the above second purpose, this application provides the following technical solutions:
[0027] A flame retardant nonwoven fabric is prepared by the above preparation process. The flame retardant nonwoven fabric has good flame retardant properties and can still maintain good flame retardant properties after multiple frictions.
[0028] In summary, this application includes the following beneficial technical effects:
[0029] 1. The present application provides a preparation process for a flame-retardant non-woven fabric, wherein the non-woven fabric substrate is treated with a flame-retardant finishing liquid containing a metal hydroxide, sprayed with a spraying liquid containing cyclodextrin, and cured with a curing agent, and a flame-retardant layer is formed on the surface of the non-woven fabric fiber using cyclodextrin to improve the flame-retardant properties of the flame-retardant non-woven fabric; at the same time, cyclodextrin can slow down the loss of metal hydroxide, so that the flame-retardant non-woven fabric can still maintain good flame-retardant properties after multiple frictions;
[0030] 2. By adding metal oxides and polyamino acids into the spraying liquid, the flame retardant properties of the flame retardant nonwoven fabric are further improved, and the loss of metal hydroxide is further slowed down, so that the flame retardant nonwoven fabric can still maintain good flame retardant properties after multiple frictions;
[0031] 3. The present application provides a flame-retardant non-woven fabric with good flame-retardant properties, a limiting oxygen index of more than 40%, a damaged length of less than 50 mm, and after 2000 frictions, the change rates of the limiting oxygen index and the damaged length are both less than 2%. DETAILED DESCRIPTION
[0032] The present application is further described in detail below in conjunction with examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.
[0033] Examples 1-3
[0034] Embodiments 1-3 respectively provide a flame retardant nonwoven fabric.
[0035] The difference between Examples 1-3 is that the composition of the flame retardant finishing liquid used to prepare the flame retardant non-woven fabric is different, as shown in Table 1.
[0036] The preparation method of the flame retardant nonwoven fabric is as follows:
[0037] 1) mixing aluminum hydroxide, polyvinyl alcohol and water to obtain a flame retardant finishing liquid, wherein the average particle size of the aluminum hydroxide is 200 nm, and the polyvinyl alcohol is PVA-217 (with a degree of polymerization of 1700-1750 and a degree of alcoholysis of 87%-89%);
[0038] 2) Soak the polypropylene non-woven fabric substrate in the flame retardant finishing liquid at 40°C for 2 hours, take it out and squeeze out the excess liquid, and dry it at 100°C;
[0039] 3) Spraying a coating liquid onto the dried nonwoven fabric treated in step 2), wherein the coating liquid is a 1.5% cyclodextrin aqueous solution, wherein the cyclodextrin is β-cyclodextrin, and the coating amount is 4 g / m 2 , extruded after spraying;
[0040] 4) Soaking the non-woven fabric treated in step 3) in a curing agent solution at 60° C. for 12 hours, taking it out, washing it with alcohol, washing it with water, and drying it to obtain a flame-retardant non-woven fabric; wherein the curing agent solution is obtained by mixing toluene diisocyanate and ethyl acetate in a weight ratio of 0.2:100.
[0041] Table 1 Weight parts of each component in the flame retardant finishing liquid provided in Examples 1-3
[0042]
[0043] Embodiment 4-5
[0044] Examples 4-5 respectively provide a flame retardant nonwoven fabric, and the raw materials and preparation methods refer to Example 2. The difference between Examples 4-5 and Example 2 is that in step 3), the concentration of cyclodextrin in the spraying liquid is different, and the spraying amount of the spraying liquid is different, as shown in Table 2.
[0045] Table 2 The concentration of cyclodextrin in the spraying liquid provided by Examples 4-5 and the spraying amount of the spraying liquid
[0046] Example Cyclodextrin concentration in spray solution Spraying amount of spraying liquid 4 1% <![CDATA[5g / m 2 ]]> 5 2% <![CDATA[3g / m 2 ]]>
[0047] Example 6
[0048] Example 6 provides a flame retardant nonwoven fabric. The raw materials and preparation method refer to Example 2. The difference between Example 6 and Example 2 is that in step 1), the average particle size of aluminum hydroxide is 50 nm.
[0049] Example 7
[0050] Example 7 provides a flame retardant nonwoven fabric. The raw materials and preparation method refer to Example 2. The difference between Example 7 and Example 2 is that in step 1), the average particle size of aluminum hydroxide is 500 nm.
[0051] Example 8
[0052] Example 8 provides a flame retardant nonwoven fabric, and the preparation method is the same as that of Example 2. The difference between Example 8 and Example 2 is that in step 1), aluminum hydroxide is replaced by magnesium hydroxide.
[0053] Example 9
[0054] Example 9 provides a flame retardant nonwoven fabric, and the preparation method is the same as that of Example 2. The difference between Example 9 and Example 2 is that in step 1), the polyvinyl alcohol is PVA-124 (degree of polymerization is 2600, degree of alcoholysis is 98%-99%).
[0055] Example 10
[0056] Example 10 provides a flame retardant nonwoven fabric, and the preparation method is the same as that of Example 2. The difference between Example 10 and Example 2 is that in step 3), the spraying liquid also includes polyglutamic acid, and the concentration of polyglutamic acid in the spraying liquid is 3%.
[0057] Embodiment 11
[0058] Example 11 provides a flame retardant nonwoven fabric, and the preparation method refers to Example 2. The difference between Example 11 and Example 2 is that in step 3), the spraying liquid also includes zinc oxide with an average particle size of 20 μm, and the concentration of zinc oxide in the spraying liquid is 2%.
[0059] Example 12
[0060] Example 12 provides a flame-retardant nonwoven fabric. The raw materials and preparation method are the same as those of Example 11. The difference between Example 12 and Example 11 is that in step 3), the average particle size of zinc oxide is 0.5 μm.
[0061] Example 13
[0062] Example 13 provides a flame-retardant nonwoven fabric. The raw materials and preparation method refer to Example 11. The difference between Example 13 and Example 11 is that in step 3), the average particle size of zinc oxide is 200 μm.
[0063] Embodiment 14
[0064] Example 14 provides a flame retardant nonwoven fabric, and the preparation method refers to Example 2. The difference between Example 14 and Example 2 is that in step 3), the spray liquid also includes polyglutamic acid and zinc oxide with an average particle size of 20 μm, the concentration of polyglutamic acid in the spray liquid is 3%, and the concentration of zinc oxide in the spray liquid is 2%.
[0065] Embodiment 15
[0066] Example 15 provides a flame retardant nonwoven fabric, and the preparation method is the same as that of Example 14. The difference between Example 15 and Example 14 is that in step 3), polyglutamic acid is replaced by polylysine, and zinc oxide is replaced by magnesium oxide.
[0067] Comparative Example 1
[0068] Comparative Example 1 provides a flame retardant nonwoven fabric, and the specific preparation method is as follows:
[0069] 1) Aluminum hydroxide, polyvinyl alcohol and water are mixed in a weight ratio of 2:15:75 to obtain a flame retardant finishing liquid, wherein the average particle size of the aluminum hydroxide is 200 nm, and the polyvinyl alcohol is PVA-217 (polymerization degree is 1700-1750, and alcoholysis degree is 87%-89%);
[0070] 2) Soak the polypropylene non-woven fabric substrate in the flame retardant finishing liquid at 40° C. for 2 hours, take it out and squeeze out the excess liquid;
[0071] 3) soaking the non-woven fabric treated in step 2) in a curing agent solution at 60° C. for 12 hours, taking it out, washing it with alcohol, washing it with water, and drying it to obtain a flame-retardant non-woven fabric; wherein the curing agent solution is obtained by mixing toluene diisocyanate and ethyl acetate in a weight ratio of 0.2:100.
[0072] Comparative Example 2
[0073] Comparative Example 2 provides a flame retardant nonwoven fabric, and the preparation method is the same as that of Example 2. The difference between Comparative Example 2 and Example 2 is that in step 1), polyvinyl alcohol is replaced by polyacrylic acid.
[0074] Performance Testing
[0075] The following performance tests were performed on the flame-retardant nonwoven fabrics provided in Examples 1-15 and Comparative Examples 1-2 of the present application:
[0076] The breaking strength test was carried out in accordance with GB / T 24218.3-2010 “Test methods for textile nonwovens”;
[0077] According to GB / T 5455-2014 “Determination of vertical damage length, smoldering and afterflaming time of textile combustion performance”, the limiting oxygen index (LOI) test and the damage length test were carried out. The flame-retardant non-woven fabric samples were rubbed using a Martindale abrasion tester, and the flame-retardant non-woven fabric samples before rubbing treatment and after 2000 frictions were tested respectively.
[0078] The test data are shown in Table 3.
[0079] Table 3 Test results of longitudinal breaking strength, limiting oxygen index (before and after 2000 frictions) and damaged length (before and after 2000 frictions) of Examples 1-15 and Comparative Examples 1-2
[0080]
[0081]
[0082] Among them, the percentage of change = |Results after 2000 frictions - Results before 2000 frictions| ÷ Results before 2000 frictions × 100%
[0083] The following is a detailed description of this application in conjunction with the test data provided in Table 3.
[0084] Examples 1-3 investigated the effects of the contents of the various components in the flame retardant finishing liquid on the properties of the flame retardant nonwoven fabric. The results showed that changing the amounts of metal hydroxide, polyvinyl alcohol and water added to the flame retardant finishing liquid had a slight effect on the properties of the flame retardant nonwoven fabric, but all were able to meet the requirements of use, and Example 2 was relatively superior.
[0085] Taking Example 2 as a control, Examples 4-5 investigated the effects of the concentration and amount of cyclodextrin in the spray liquid on the performance of the flame retardant nonwoven fabric. The results showed that the concentration of cyclodextrin and the amount of spray liquid had a slight effect on the performance of the flame retardant nonwoven fabric, but both could meet the use requirements, and Example 2 was relatively superior.
[0086] Taking Example 2 as a control, Examples 6-7 investigated the effect of the particle size of the metal hydroxide on the performance of the flame retardant nonwoven fabric. The results showed that the particle size of the metal hydroxide had a slight effect on the performance of the flame retardant nonwoven fabric. Too large or too small a particle size was not conducive to the adhesion of the metal hydroxide to the surface of the nonwoven fabric. Example 2 was relatively superior.
[0087] Taking Example 2 as a control, Example 8 investigated the effect of the type of metal hydroxide on the performance of the flame retardant non-woven fabric. The results showed that after replacing aluminum hydroxide with magnesium hydroxide, the flame retardant properties of the flame retardant non-woven fabric were slightly reduced, but could still meet the use requirements.
[0088] Taking Example 2 as a control, Example 9 investigated the effects of the degree of polymerization and alcoholysis degree of polyvinyl alcohol on the performance of the flame retardant nonwoven fabric. Compared with Example 2, the flame retardant performance of the flame retardant nonwoven fabric in Example 9 decreased more significantly after multiple frictions, indicating that when the degree of polymerization and alcoholysis degree of polyvinyl alcohol are within an appropriate range, the adhesion stability of the metal hydroxide on the nonwoven fabric can be effectively improved.
[0089] On the basis of Example 2, Example 10 added polyamino acid to the spraying liquid. The results showed that adding polyamino acid alone to the spraying liquid had little effect on the performance of the flame retardant nonwoven fabric.
[0090] On the basis of Example 2, metal oxides were added to the spray liquid in Examples 11-13. The results showed that after adding metal oxides, the flame retardant properties of the flame retardant non-woven fabric were improved. This was because the metal oxides formed a flame retardant barrier on the surface of the non-woven fabric, further improving the flame retardant properties of the non-woven fabric. At the same time, after multiple frictions, the flame retardant properties of the flame retardant non-woven fabric decreased less. This was because the metal oxides formed a wear-resistant layer on the surface of the non-woven fabric, further reducing the loss of metal hydroxide flame retardants in the non-woven fabric substrate during the friction process.
[0091] Examples 11-13 also investigated the effect of the particle size of the metal oxide on the performance of the flame retardant nonwoven fabric. The results showed that the particle size of the metal oxide had a slight effect on the performance of the flame retardant nonwoven fabric, and Example 11 was relatively superior.
[0092] On the basis of Example 2, Example 14 simultaneously added polyamino acid and metal oxide to the spray liquid. Combining the results of Examples 2, 10 and 11, it can be seen that the polyamino acid and the metal oxide work together to significantly improve the flame retardant properties of the non-woven fabric, and after multiple frictions, the flame retardant properties of the flame retardant non-woven fabric are slightly reduced, and the percentage changes in the limiting oxygen index and the damage length are both below 2%. This is because there is a chelating effect between the polyamino acid and the metal oxide, which helps to improve the compatibility between the metal oxide and the non-woven fabric.
[0093] Taking Example 14 as a control, Example 15 investigated the influence of the types of polyamino acids and metal oxides on the performance of flame retardant nonwoven fabrics. The results showed that after replacing polyglutamic acid with polylysine and zinc oxide with magnesium oxide, the performance of the flame retardant nonwoven fabric changed slightly, but still met the use requirements.
[0094] Compared with Example 2, the flame retardant properties of the flame retardant non-woven fabric in Comparative Example 1 are significantly reduced, indicating that spraying cyclodextrin helps to improve the flame retardant properties of the non-woven fabric. At the same time, the flame retardant properties of the flame retardant non-woven fabric in Comparative Example 1 are significantly reduced after multiple frictions, indicating that cyclodextrin plays a role in slowing down the loss of metal hydroxide on the surface of the non-woven fabric fibers.
[0095] Taking Example 2 as a control, polyvinyl alcohol was replaced with polyacrylic acid in Comparative Example 2. The results showed that the flame retardant performance of the flame retardant non-woven fabric in Comparative Example 2 decreased more significantly after multiple frictions, indicating that compared with polyacrylic acid, polyvinyl alcohol is more helpful in improving the adhesion stability of metal hydroxides on the non-woven fabric.
[0096] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A process for preparing a flame retardant nonwoven fabric, characterized in that: The following steps are involved: S1. Mixing metal hydroxide, polyvinyl alcohol and water in a weight ratio of (1-3): (10-20): (70-80) to obtain a flame retardant finishing liquid; S2. The nonwoven fabric substrate is immersed in the flame retardant finishing solution, removed and dried; S3. Spraying a coating liquid onto the dried nonwoven fabric after treatment in step S2, wherein the coating liquid comprises a cyclodextrin solution; S4. The nonwoven fabric treated in step S3 is immersed in a curing agent solution, taken out, washed and dried to obtain the flame-retardant nonwoven fabric; The metal hydroxide is selected from one or both of magnesium hydroxide and aluminum hydroxide, the average particle size of the metal hydroxide is 50-500 nm, and the curing agent is selected from one or more of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate.
2. The process for preparing the flame-retardant nonwoven fabric according to claim 1, characterized in that: The degree of polymerization of the polyvinyl alcohol is 1700-1750, and the degree of alcoholysis is 87%-89%.
3. The process for preparing the flame-retardant nonwoven fabric according to claim 1, characterized in that: The cyclodextrin solution is a cyclodextrin aqueous solution with a concentration of 1-2%, and the spraying amount of the spraying liquid is 3-5g / m 2 .
4. The process for preparing the flame-retardant nonwoven fabric according to claim 1, characterized in that: The curing agent solution is obtained by mixing a curing agent and a solvent in a weight ratio of (0.1-0.3):100, and the solvent is selected from one or both of acetone and ethyl acetate.
5. The process for preparing the flame-retardant nonwoven fabric according to claim 1, characterized in that: The spraying liquid also includes metal oxides, and the concentration of the metal oxides in the spraying liquid is 1-3%.
6. The process for preparing the flame-retardant nonwoven fabric according to claim 5, characterized in that: The metal oxide is selected from one or more of zinc oxide, aluminum oxide and magnesium oxide, and the average particle size of the metal oxide is 0.5-200 μm.
7. The process for preparing the flame-retardant nonwoven fabric according to claim 1, characterized in that: The spraying liquid also includes polyamino acid, and the concentration of the polyamino acid in the spraying liquid is 2-4%.
8. The process for preparing the flame-retardant nonwoven fabric according to claim 7, characterized in that: The polyamino acid is selected from one or more of polyglutamic acid, polylysine and polyaspartic acid.
9. A flame retardant nonwoven fabric, characterized in that: The flame retardant nonwoven fabric is prepared by the preparation process of the flame retardant nonwoven fabric according to any one of claims 1 to 8.
Citation Information
Patent Citations
Water-based halogen-free flame-retardant paper and preparation method thereof
CN102619139A
Environment-friendly and flame-retardant coating, preparation method thereof and environment-friendly and flame-retardant coating layer
CN105647304A